2000
DOI: 10.1007/s002109900187
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, but not vasopressin V2 receptor-mediated vasodilation, modulates vasopressin-induced renal vasoconstriction in rats

Abstract: The renal vascular response to vasopressin and its modulation were evaluated in vivo by infusing the peptide directly into the renal artery of anaesthetized rats. The intra-renal artery (i.r.a) infusion of vasopressin induced a dose-dependent decrease in renal blood flow. Vasoconstriction was obvious at a dose of 3 ng/kg per min and reached a maximum at 100 ng/kg per min. The dose required for a half-maximal response (ED50) was 24+/-4 ng/kg per min (mean+/-SEM, n=8), corresponding to an estimated concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…This agrees with previous studies indicating that in vivo, vasoconstriction of renal arterioles can be induced only by high, nonphysiological doses (nanomolar range) of AVP (35), whereas low physiological doses (picomolar range) are efficient in vitro (36). One possible explanation is the attenuation of AVPinduced vasoconstriction by nitric oxide release in vivo (37). In addition, we found that the patterns of cell proliferation associated with prolonged hyperosmotic stimulation or AVP infusion (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with previous studies indicating that in vivo, vasoconstriction of renal arterioles can be induced only by high, nonphysiological doses (nanomolar range) of AVP (35), whereas low physiological doses (picomolar range) are efficient in vitro (36). One possible explanation is the attenuation of AVPinduced vasoconstriction by nitric oxide release in vivo (37). In addition, we found that the patterns of cell proliferation associated with prolonged hyperosmotic stimulation or AVP infusion (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are compatible with the assumption that V 1a receptors on peripheral arterial and renal vasculature mediate the vasoconstrictive action of AVP (Birnbaumer, 2000; Loichot et al, , whose levels are elevated in CHF (Szatalowicz et al, 1981;Goldsmith et al, 1983). The vasoconstrictive action of AVP is mediated by the V 1a -receptor and may be modulated by local release of nitric oxide and prostaglandins (Loichot et al, 2000). In pathological concentrations, AVP also decreases total RBF and GFR as a part of the generalized vasoconstriction induced by the peptide (Christiansen et al, 2001).…”
supporting
confidence: 86%